The Many Faces of JAKs and STATs Within the COVID-19 Storm - Grant, Alice H.; Estrada, Armando; Ayala-Marin, Yoshira M.; Alvidrez-Camacho, America Y.; Rodriguez, Georgialina; Robles-Escajeda, Elisa; Cadena-Medina, Denisse A.; Rodriguez, Alejandro C.; Kirken, Robert A. (Frontiers in Immunology, 2021)
The positive-sense single stranded RNA virus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), resulted in a global pandemic with horrendous health and economic consequences not seen in a century. At a finer scale, immunologically, many of these devastating effects by SARS-CoV-2 can be traced to a ‘cytokine storm’ resulting in the simultaneous activation of Janus Kinases (JAKs) and Signal Transducers and Activators of Transcription (STAT) proteins downstream of the many cytokine receptor families triggered by elevated cytokines found in Coronavirus Disease 2019 (COVID-19). In this report, cytokines found in the storm are discussed in relation to the JAK-STAT pathway in response to SARS-CoV-2 and the lessons learned from RNA viruses and previous Coronaviruses (CoVs). Therapeutic strategies to counteract the SARS-CoV-2 mediated storm are discussed with an emphasis on cell signaling and JAK inhibition.